Phorbol ester receptors and protein kinase C in primary neuronal cultures: development and stimulation of endogenous phosphorylation (The Rockefeller University Press, 1986)
Embryonic rat neurons cultured in defined medium, essentially in the absence of glia, were highly enriched in phorbol ester receptors. The neurons displayed a single class of phorbol 12,13-dibutyrate binding sites with a maximum binding capacity, after 10 d in culture, of 18.6 pmol/mg protein and an apparent dissociation constant of 7.1 nM. Phorbol ester binding sites were associated with protein kinase C, which represented a major protein kinase activity in primary neuronal cultures. Ca2+-phosphatidylserine-sensitive phosphorylation of endogenous substrates was more marked than that observed in the presence of cyclic AMP or Ca2+ and calmodulin. Phorbol ester receptors and protein kinase C levels were critically dependent on the culture age. Thus, about a 20-fold increase in binding sites occurred during the first week in culture and was accompanied by a corresponding increase in Ca2+-phosphatidylserine-sensitive protein phosphorylation in soluble neuronal extracts. These changes largely paralleled a similar rise in phorbol ester binding during fetal development in vivo. The apparent induction of phorbol ester receptors was specific relative to other cellular proteins and could be inhibited by cycloheximide or Actinomycin D. Phosphorylation of endogenous substrates in intact cultured neurons paralleled the age-dependent increase in protein kinase C. Furthermore, 32P incorporation into several major phosphoproteins was markedly augmented by treating the neuronal cultures with phorbol esters. Such phosphorylation events may provide a clue to the significance of protein kinase C in developing neurons.